Analyzing and Optimizing Adaptive Modulation Coding Jointly With ARQ for QoS-Guaranteed Traffic - Xin Wang; Qingwen Liu; Giannakis, G.B. (IEEE transactions on vehicular technology, 2007)
A cross-layer design is developed for quality-of-service (QoS)-guaranteed traffic. The novel design jointly exploits the error-correcting capability of the truncated automatic repeat request (ARQ) protocol at the data link layer and the adaptation ability of the adaptive modulation and coding (AMC) scheme at the physical layer to optimize system performance for QoS-guaranteed traffic. The queuing behavior induced by both the truncated ARQ protocol and the AMC scheme is analyzed with an embedded Markov chain. Analytical expressions for performance metrics such as packet loss rate, throughput, and average packet delay are derived. Using these expressions, a constrained optimization problem is solved numerically to maximize the overall system throughput under the specified QoS constraints